2023
DOI: 10.1097/pxr.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe congenital femoral deficiency: Does surgical intervention enhance prosthetic function?

Peter Calder,
Ahmed Elsheikh,
George Cross
et al.

Abstract: Background & Objective: The purpose of this study was to evaluate prosthetic outcome in patients with severe congenital femoral deficiency and the potential benefits of surgical intervention on prosthetic fitting and gait. Methods: A retrospective review identified 26 active case records with a proximal femoral focal deficiency using a prosthesis. Validated outcome measures evaluated comfort, function, and prosthetic use and quality-of-life assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“… 108 With no long-term studies, the question remains as to whether surgical intervention enhances functional outcome. Calder et al 109 undertook an observational descriptive study in an attempt to demonstrate the effect of surgical intervention on quality of life and limb function in cases of severe CFD. They concluded that surgical intervention appeared to improve function, with scores declining into adulthood but not significantly.…”
Section: Congenital Lower Limb Deficiency—amputation and Prosthetic F...mentioning
confidence: 99%
“… 108 With no long-term studies, the question remains as to whether surgical intervention enhances functional outcome. Calder et al 109 undertook an observational descriptive study in an attempt to demonstrate the effect of surgical intervention on quality of life and limb function in cases of severe CFD. They concluded that surgical intervention appeared to improve function, with scores declining into adulthood but not significantly.…”
Section: Congenital Lower Limb Deficiency—amputation and Prosthetic F...mentioning
confidence: 99%